Aligning ESG Ratings and SDGs in the MENA Region: Challenges and Insights Through a Fuzzy Delphi Multi-Criteria Approach - Hayet Benhamida; Zoubida Benmamoun; Vernika Agarwal; Youssef Raouf; Arshia Kaul (International Journal of Mathematical, Engineering and Management Sciences)
This research paper looks at the intricate interrelationships between environmental, social and governance issues and government debt levels in the Middle East and North Africa region. The paper examines the emergence of various approaches in shaping government debt levels as part of developing sustainable models for this area. The study highlights comprehending problems in relation to how Environment, Social and Governance and sustainable development goals assessments and public-sector indebtedness should be integrated. The aim of this study is to identify challenges that hinder a smooth integration of this system required for comprehensive credit assessment informed by global best practices. Delphi technique is used to outline key areas relating to environmentally sustainable development goals inclusion into sector sovereign credit rating with specific reference to environmental, social and corporate governance ratings. This analysis employs a fuzzy Delphi method to define these challenges in order to accommodate built-in uncertainty associated with each problem area and also obtain weights for them all. Furthermore, Fuzzy Best Worst Methodology has been applied in this study to classify these problems according to their degree of importance. By integrating objectives with resources into lending strategies, we already have an improved combined/contingent approach within our midst. Fuzzy method is therefore an integral part of its use to integrate vagueness and ambiguity of the decision maker's opinions.